Теорія та аплікація логістичної концепції сталого розвитку урботуризму - Смирнов, Ігор Георгійович (Київський національний університет імені Тараса Шевченка, 2017)
Goal. To reveal the theoretical foundations and directions of the practical application of the logistic concept of urban tourism sustainable development on the example of Ukrainian cities of Kyiv and Lviv. The research methodology is to apply the provisions of the author’s logistic concept of sustainable tourism development (in particular, principal, regional and strategic logistic models) to the practice of efficient organization of tourist streams and routes in cities. Results. The components of the logistic conception of sustainable development of urboturism are described and applied to the problems of tourism sustainable development in the cities of Ukraine on the example of Kyiv and Lviv. Scientific novelty. For the first time, the logistic concept of sustainable tourism development in cities (Urboturism) was proposed on the basis of a logistic model of effective organization of tourist space, in particular in the central and historical districts of cities. Practical significance. It is the application of the theoretical logistic concept of sustainable development of urban tourism to the problems of tourism practice in the cities of Ukraine on the example of Kyiv and Lviv and the provision of recommendations for solving the problem of tourist overloading, as well as the problems of waste (rubbish) accumulation and recycling, which Lviv faced in the summer of 2017.

Мета. Розкрити теоретичні основи та напрямки практичного застосування логістичної концепції сталого розвитку урботуризму на прикладі українських міст Києва та Львова. Методика дослідження полягає у застосуванні положень авторської логістичної концепції сталого розвитку туризму (зокрема, принципової, розгорнутої та стратегічної логістичних моделей) до практики ефективної організації туристичних потоків та маршрутів у містах. Результати. Охарактеризовано складники логістичної концепції сталого розвитку урботуризму та виконано їхню аплікацію до проблем сталого розвитку туризму у містах України на прикладі Києва та Львова. Наукова новизна. Вперше запропоновано логістичну концепцію сталого розвитку туризму у містах (урботуризму) на підставі логістичної моделі ефективної організації туристичного простору, зокрема у центральних та історичних частинах міст. Практична значимість. Полягає у застосуванні теоретичної логістичної концепції сталого розвитку урботуризму до проблем туристичної практики у містах України на прикладі Києва та Львова та наданні рекомендацій щодо вирішення проблеми туристичного перевантаження, а також проблеми накопичення та переробки відходів (смітття), з якими влітку 2017 р. зіштовхнулося м. Львів.
Theory and Application of the Logistic Concept of Sustainable Development of Urban Tourism
Теория и аппликация логистической концепции устойчивого развития урботуризма
Keywords: урботуризм; логістика; зворотна логістика; туристичне споживання; міські відходи; рециркуляція; Urboturism; logistics; reverse logistics; tourist consumption; urban waste; recycling